On the propagation of waves in the elasto- plastic medium with complex loading - Thang, Duong Tat; Bich, Dao Huy (Vietnam Journal of Mechanics, 1987)
In this paper is studied the propagation of waves in the infinite tridinmensial plastic medium with compels loading, using the theory of elasto - plastic definition processes.